Beauty pays: Why attractive people are more sucessful - Hamermesh, Daniel S. (New Jersey Princeton University Press, 2011)
Most of us know there is a payoff to looking good, and in the quest for beauty we spend countless hours and billions of dollars on personal grooming, cosmetics, and plastic surgery. But how much better off are the better looking? Based on the evidence, quite a lot. The first book to seriously measure the advantages of beauty, Beauty Pays demonstrates how society favors the beautiful and how better-looking people experience startling but undeniable benefits in all aspects of life. Noted economist Daniel.